Curiosity-Based Interventions Increase Everyday Functioning Score But Not Serum BDNF Levels in a Cohort of Healthy Older Adults - Grossberg, Allison N.; Bettcher, Brianne M.; Gorgens, Kim A.; Ledreux, Aurélie (Frontiers in Aging, 2021)
An enriched environment is effective in stimulating learning and memory in animal models as well as in humans. Environmental enrichment increases brain-derived neurotrophic factor (BDNF) in aged rats and reduces levels of Alzheimer-related proteins in the blood, including amyloid-beta peptides and misfolded toxic forms of tau. To address whether stimulation of curiosity, which is a form of enrichment, may provide a buffer against Alzheimer’s disease (AD), we measured levels of biomarkers associated with AD at baseline and after a 6-week intervention in older adults (>65 years of age) randomized to one of three different intervention conditions. Specifically, in this pilot study, we tested the effectiveness of a traditional, structured learning environment compared to a self-motivated learning environment designed to stimulate curiosity. There were no significant differences from baseline to post-intervention in any of the groups for Aβ42/Aβ40 ratio or t-tau (total-tau) plasma levels. Serum BDNF levels decreased significantly in the Control group. Interestingly, individuals who had the lowest serum BDNF levels at baseline experienced significantly higher increases in BDNF over the course of the 6-week intervention compared to individuals with higher serum BDNF levels at baseline. As expected, older individuals had lower MoCA scores. Years of education correlated negatively with Aβ levels, suggesting a protective effect of education on levels of this toxic protein. ECog scores were negatively correlated with BDNF levels, suggesting that better performance on the ECog questionnaire was associated with higher BDNF levels. Collectively, these findings did not suggest that a 6-week cognitive training intervention focused on curiosity resulted in significant alterations in blood biomarkers but showed interesting correlations between cognitive scores and BDNF levels, further supporting the role of this trophic factor in brain health in older adults.